Legal Counceling on Early Marriage Prevention in the Context of Reproductive Health Protection for Junior High School Students - Putri, Rizha Claudilla; Handayani, Sri; Rasyid, Muhamad; Azani, Adila (Universitas Putra Indonesia YPTK Padang, 2025)
The high national prevalence of early marriage in Indonesia, affecting 5.90% of women aged 20-24 who were married before 18, and particularly 8.45% in South Sumatra, poses a significant risk to adolescent physical and mental well-being. Early marriage often leads to severe health consequences like high maternal and infant mortality rates, preeclampsia, and anemia due to an immature reproductive system. The current minimum marriage age is 19 years for both genders as regulated by Law Number 16/2019. This community service aimed to address the lack of knowledge among adolescents on this critical issue. The activity at Junior High School 23 Palembang utilized the Participatory Action Research (PAR) approach, focusing on legal counseling and interactive discussions for ninth-grade students. The core material covered legal provisions, social, mental, and reproductive health impacts, and the roles of parents and schools. A key finding was the significant improvement in student understanding, as evidenced by the evaluation: the average score increased from 56.25 on the pre-test to 90.82 on the post-test, an increase of 34.58 points. This result confirms the effectiveness of the legal counseling in enhancing students' legal knowledge and fostering a positive attitude to reject early marriage and act as agents of change.